Cytochrome P450 3A4 suppression by epimedium and active compound kaempferol leads to synergistic anti-inflammatory effect with corticosteroid - Li, Ke; Yu, Xiu-Hua; Maskey, Anish R.; Musa, Ibrahim; Wang, Zhen-Zheng; Garcia, Victor; Guo, Austin; Yang, Nan; Srivastava, Kamal; Dunkin, David; Li, Jun-Xiong; Guo, Longgang; et al. (Frontiers in Pharmacology, 2023)
Cytochrome P450 (CYP) 3A4 is a major drug metabolizing enzyme for corticosteroids (CS). Epimedium has been used for asthma and variety of inflammatory conditions with or without CS. It is unknown whether epimedium has an effect on CYP 3A4 and how it interacts with CS. We sought to determine the effects of epimedium on CYP3A4 and whether it affects the anti-inflammatory function of CS and identify the active compound responsible for this effect. The effect of epimedium on CYP3A4 activity was evaluated using the Vivid® CYP high-throughput screening kit. CYP3A4 mRNA expression was determined in human hepatocyte carcinoma (HepG2) cells with or without epimedium, dexamethasone, rifampin, and ketoconazole. TNF-α levels were determined following co-culture of epimedium with dexamethasone in a murine macrophage cell line (Raw 264.7). Active compound (s) derived from epimedium were tested on IL-8 and TNF-α production with or without corticosteroid, on CYP3A4 function and binding affinity. Epimedium inhibited CYP3A4 activity in a dose-dependent manner. Dexamethasone enhanced the expression of CYP3A4 mRNA, while epimedium inhibited the expression of CYP3A4 mRNA and further suppressed dexamethasone enhancement of CYP3A4 mRNA expression in HepG2 cells (p＜0.05). Epimedium and dexamethasone synergistically suppressed TNF-α production by RAW cells (p<0.001). Eleven epimedium compounds were screened by TCMSP. Among the compounds identified and tested only kaempferol significantly inhibited IL-8 production in a dose dependent manner without any cell cytotoxicity (p<0.01). Kaempferol in combination with dexamethasone showed complete elimination of TNF-α production (p<0.001). Furthermore, kaempferol showed a dose dependent inhibition of CYP3A4 activity. Computer docking analysis showed that kaempferol significantly inhibited the catalytic activity of CYP3A4 with a binding affinity of -44.73kJ/mol. Inhibition of CYP3A4 function by epimedium and its active compound kaempferol leads to enhancement of CS anti-inflammatory effect